Nominal and Real Wages in the UK, 1750 - 2015: Mean Reversion, Persistence and Structural Breaks - Guglielmo Maria Caporale; Luis A. Gil-Alana (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper analyses the stochastic properties of UK nominal and real wages over the period 1750-2015 using fractional integration techniques. Both the original series and logged ones are analysed. The results generally suggest that nominal wages exhibit a higher degree of persistence, which reflects relatively long lags between inflation and wage adjustments. Endogenous break tests are also carried out and various structural breaks are identified in both series. On the whole the corresponding subsample estimates imply an increase over time in the degree of persistence of both series.
Keywords: C12; C13; C22; J30; 330; nominal and real wages; mean reversion; persistence; fractional integration; structural breaks